Study of the Maternal Mortality Burden from Indirect Causes - Lisbeth Fernández González; José Luis Peñalvo; Miguel Ángel Martínez Morales; Armando Humberto Seuc Jo; Delia Gálvez Medina; Alain Francisco Morejón Giraldoni (Revista Finlay, 2022)
Background: the characterization of the mortality burden is essential information for planning and setting priorities in health, monitoring and evaluating intervention programs and identifying groups of women at higher risk. Objective: to determine the maternal deaths burden from indirect causes in Cuba in the period 2005-2020. Methods: a descriptive cross-sectional study of annual series was carried out. The universe was the total number of indirect maternal deaths registered during the studied years. The variables used in the study were: basic cause of death and age. For each series, the years of life potentially lost due to mortality, their percentage and average, as well as the trend over the years, were calculated. Results: during 2005-2020, 269 women died in Cuba due to indirect causes. Premature deaths quantified 13,972 years of life potentially lost, with an annual average of 874 years, which represented an average of 51 years not lived for each deceased. The indirect causes that generated more years of life lost were the group of other indirect causes, 341 years on average, and diseases of the circulatory system, 247. Conclusion: the causes of death with the greatest impact on life expectancy in the Cuban population coincided with the causes with the highest number of deaths, which shows that there are no great differences in the ages at which one dies between the different causes. The women who died at younger ages were those in the group with other indirect causes, which, together with the circulatory system diseases, showed a tendency to increase over time.